The physicochemical properties of local Indonesia honey Trigona and Cerana produced in North Lombok, West Nusa Tenggara - Rizki Ameliya; Erryana Martati; Siti Narsito Wulan (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Trigona and Cerana honey production in North Lombok was 24,751 L and 41,589 L, respectively, in 2020. The physicochemical properties of honey vary depending on the types of plants from which the bee collects nectar, climatic conditions and geographical region. Thus, a worldwide standard for honey bee products has yet to be determined. This research aims to analyze the physicochemical properties of honey originally produced in North Lombok. The results showed that moisture content, acidity, ash, pH, viscosity and colour of Trigona honey were significantly different from Cerana honey (p<0,05); meanwhile, reducing sugar, insoluble solids, and total phenolic did not differ between the two honey (p>0,05). Moisture content (27.56%), acidity (281.15 meq/kg), insoluble solids (1.87%) and total phenolic (19 mg GAE/g) in Trigona honey were higher than those in Cerana (moisture content (26.3%), insoluble solids (1.38%), total phenolic (16.56 mg GAE/g)). Meanwhile, reducing sugar (17.71%), pH (3.25), ash (0.85%), viscosity (596.33 cP), and diastase activity (0.1692 DN) of Trigona honey were lower than those in Cerana (reducing sugar (18.28%), pH (3.25), ash (1.35%), viscosity (956.33 cP) and diastase activity (31.28 DN)). The °Hue value of Trigona and Cerana honey was 53.5 and 65, which appears yellow red for both kinds of honey.